2009
DOI: 10.1332/174426409x395402
|View full text |Cite
|
Sign up to set email alerts
|

Increasing capacity for knowledge translation: understanding how some researchers engage policy makers

Abstract: The potential for research to influence policy, and for researchers to influence policy actors, is significant. The purpose of this qualitative study was to explore the experiences of health services researchers engaging in (or not able to engage in) policy-relevant research. Semistructured telephone interviews were completed with 23 experienced researchers.The results paint a complex and dynamic picture of the policy environment and the relationship between government officials and academic researchers. Eleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 22 publications
2
46
0
Order By: Relevance
“…Kothari et al 75 suggest that the importance of the end-user's underpinning value base is key to determining utilisation. Within the context of multidisciplinary working, as is typical within public health, the differing value bases of differing stakeholders may wrestle for credence in relation to a specific issue.…”
Section: Non-instrumental Use Of Research Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…Kothari et al 75 suggest that the importance of the end-user's underpinning value base is key to determining utilisation. Within the context of multidisciplinary working, as is typical within public health, the differing value bases of differing stakeholders may wrestle for credence in relation to a specific issue.…”
Section: Non-instrumental Use Of Research Evidencementioning
confidence: 99%
“…Recent literature has emphasised the importance of interactions between researchers and practitioners 75,79 and there has, increasingly, been a move towards collaborative approaches to knowledge translation and research utilisation. It has been argued that the use of a more participatory approach enables a more nuanced understanding of context, a shared enactment of facilitation and transformative leadership.…”
Section: Exchanging Knowledge Relational Approaches and Complexitymentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of research studies have been undertaken -predominantly applying survey and interview methodologies with either research producers or policymakers (public servants and/or elected officials), and some with larger sample sizes than others -to identify what appears to predict research use by policymakers (for example, Huberman, 1990;Landry et al, 2001a;Kothari et al, 2009;Bogenschneider & Corbett, 2010;Cherney & McGee, 2011;Haynes et al 2011a and2011b). Few of the studies reviewed seem to have explored the processes around identified characteristics or issues -instead presenting them more as "factors" that act as "barriers" or "facilitators" to research utilisation.…”
Section: Barrier and Facilitators To Research Utilisation Identified mentioning
confidence: 99%
“…For example, academic researchers interviewed by Kothari et al, (2009) indicated that the nature of working with government, which is typically characterised by short funding cycles, a crisis orientation towards policy work, and frequent turnover in staff, is inherently at odds with investing the time required to build mutual trust and understanding, and the kinds of communication that support quality relationship-building.…”
Section: Linkage-specific Research Insightsmentioning
confidence: 99%